2014
DOI: 10.1128/iai.01847-14
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei Capsular Polysaccharide Conjugates Provide Protection against Acute Melioidosis

Abstract: bBurkholderia pseudomallei, the etiologic agent of melioidosis, is a CDC tier 1 select agent that causes severe disease in both humans and animals. Diagnosis and treatment of melioidosis can be challenging, and in the absence of optimal chemotherapeutic intervention, acute disease is frequently fatal. Melioidosis is an emerging infectious disease for which there are currently no licensed vaccines. Due to the potential malicious use of B. pseudomallei as well as its impact on public health in regions where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 45 publications
(72 reference statements)
1
75
0
Order By: Relevance
“…While the constitutively expressed capsule and LPS are lead vaccine targets for B. mallei and B. pseudomallei (110)(111)(112)(113)(114), the results of our passive-transfer experiments with adsorbed immune serum demonstrate the protective value of antigens selectively expressed in vivo during vaccination with the batA KO mutant. The data show that a single dose of immune serum depleted of antibodies binding to whole B. mallei bacteria cultured in vitro provides significant protection against lethal challenge during acute and chronic infection (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…While the constitutively expressed capsule and LPS are lead vaccine targets for B. mallei and B. pseudomallei (110)(111)(112)(113)(114), the results of our passive-transfer experiments with adsorbed immune serum demonstrate the protective value of antigens selectively expressed in vivo during vaccination with the batA KO mutant. The data show that a single dose of immune serum depleted of antibodies binding to whole B. mallei bacteria cultured in vitro provides significant protection against lethal challenge during acute and chronic infection (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The ELISA data in Fig. S5 in the supplemental material demonstrate that this treatment effectively removed antibodies against antigens constitutively expressed in vitro, including capsular polysaccharides and LPS, which are the most abundant molecules on the surface of the organism and lead targets for vaccine development in the field (110)(111)(112)(113)(114). Remarkably, the adsorbed serum, which was completely depleted of antibodies binding to laboratory-grown bacteria, retained the ability to protect against lethal aerosol exposure to WT B. mallei ATCC 23344 at a level that was comparable to that of IgG antibodies purified from whole immune serum ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, type O-polysaccharide and CPS antigens covalently linked to carrier proteins demonstrated high IgG titers and protected mice from a lethal i.p. B. pseudomallei challenge [59, 60]. Furthermore, it was demonstrated that mice co-administrated with a capsular polysaccharide (CPS) glycoconjugate and the promising subunit antigen, LolC, exhibited higher survival rates following lethal challenge compared to single administration [59].…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…However, B. pseudomallei and B. mallei are BSL3 pathogens, making the isolation of antigenic components (e.g., LPS) difficult. To avoid these complications, many researchers have turned to excluded strains of B. pseudomallei or the avirulent B. thailandensis for LPS isolation (15,20,32). Importantly, the structure of B. thailandensis LPS has been shown to be nearly identical to that of B. pseudomallei and is able to protect against lethal B. pseudomallei challenge (32,33).…”
Section: Use Of Novel Burkholderia Antigens For Nanovaccinesmentioning
confidence: 99%
“…In fact, previous studies have shown that proteins alone can provide significant, albeit incomplete, protection against Burkholderia challenge (11)(12)(13)(14). However, more recent studies have shown that when immunogenic proteins are incorporated in a glycoconjugate vaccine in conjunction with the highly antigenic Burkholderia lipopolysaccharide (LPS) or capsular polysaccharide (CPS), a more robust immune response is generated (15)(16)(17)(18). Our lab has previously demonstrated that the incorporation of a glycoconjugate with the surface of a gold nanoparticle can enhance the immune response and increase protection in a murine model of inhalational glanders, a disease caused by the closely related host-adapted pathogen B. mallei (17).…”
mentioning
confidence: 99%